2013
DOI: 10.1172/jci69077
|View full text |Cite
|
Sign up to set email alerts
|

HGF upregulation contributes to angiogenesis in mice with keratinocyte-specific Smad2 deletion

Abstract: In the Methods section, the authors inadvertently provided incorrect quantitative PCR primer sequences for amplification of mouse and human HGF. The correct passage appears below.HGF levels were determined using Power SYBR Green Master Mix (Applied Biosystems) and the following custom primers: 5ʹ-AGGAACAGGGGCTTTACGTT-3ʹ (forward) and 5ʹ-GTCAAATTCATGGCCAAACC -3ʹ (reverse). Human HGF quantitative PCR assays were performed using the TaqMan probe set Hs00300159_m1.The authors regret the error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…[18][19][20] As for the expression of Npnt, Tsukasaki et al reported its suppression by Smad2, 21) while the present findings demonstrated its activation by Smad4. Together, these observations led us to speculate that the Npnt expression is also regulated by a transcription co-activator protein such as CBP/p300, and mediated by the competition between Smad2 and Smad4, though additional experiments are needed to more fully reveal the mechanism details.…”
Section: Resultssupporting
confidence: 54%
“…[18][19][20] As for the expression of Npnt, Tsukasaki et al reported its suppression by Smad2, 21) while the present findings demonstrated its activation by Smad4. Together, these observations led us to speculate that the Npnt expression is also regulated by a transcription co-activator protein such as CBP/p300, and mediated by the competition between Smad2 and Smad4, though additional experiments are needed to more fully reveal the mechanism details.…”
Section: Resultssupporting
confidence: 54%
“…Interestingly, these cells showed an increased basal Met phosphorylation when compared with the parental H69 along with upregulation of mesenchymal markers in vitro and in vivo and increased angiogenesis. The role of HGF as an inducer of EMT (10,25,26) and angiogenesis (27,28) has been reported previously.…”
Section: Discussionmentioning
confidence: 66%
“…In contrast to Smad4À/À SCCs, Smad2À/À SCCs did not have increased expression of either TGFb or VEGF [91]. This suggests that tumors with reduced Smad2 expression may be susceptible to HGF-targeted treatment, a hypothesis supported by our study showing that short term treatment of Smad2À/À skin with a c-Met (HGF receptor) inhibitor reduces Smad2 loss-associated angiogenesis [91].…”
Section: Smad2 Loss and Cancermentioning
confidence: 56%